2021
DOI: 10.24248/eahrj.v5i1.647
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Knowledge and Practices of the Community towards Corona Virus Disease 2019 in Mbale Municipality, Uganda: Across Section Study

Abstract: Background: The Corona virus disease, first identified in Wuhan city, Hubei province of China, is a respiratory illness caused by Novel Corona Virus also known as Severe Acute Respiratory Syndrome Corona Virus 2 (SARS Cov.2). The disease is characterised by; dry cough and shortness of breath with difficulty in breathing and at least 2 of the following; fever, chills, muscle pain, headache, sore throat and loss of test and smell. Uganda in general and Mbale in particular has people of diverse culture, religion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This is not surprising as long before COVID-19 rural communities were facing financial constraints as this population is estimated to be living below the poverty line [9]. Naziru et al [33] also identified masks as expensive for community members to afford them. Rural communities in Uganda are home to Our study found out that the use of masks was identified with discomforts such as breathlessness, dizziness which resulted into reduced use of masks.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…This is not surprising as long before COVID-19 rural communities were facing financial constraints as this population is estimated to be living below the poverty line [9]. Naziru et al [33] also identified masks as expensive for community members to afford them. Rural communities in Uganda are home to Our study found out that the use of masks was identified with discomforts such as breathlessness, dizziness which resulted into reduced use of masks.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Mbale district was reported to have about 4.21% among the blood donors testing positive for Hepatitis B. [8] this together with other practices in the community including but not limited to the traditional non-medical circumcision also known as "Imbalu" and its strategic location along the high way that connects Kenya to South Sudan and the Democratic Republic of Congo through Uganda with high rates of commercial sex work puts this community at such a high rate spreading diseases like HBV infection [15]. Protecting such a community requires that 90% of such a community be vaccinated this includes both the health workers and nonhealth workers.…”
Section: Problem Statementmentioning
confidence: 99%
“…Mbale district is located in the eastern region of Uganda In east Africa, approximately 225km (140 miles) northeast of the capital Kampala [15,17] According to the Uganda Bureau of statics, its population in 2019 is estimated to be 568,000 people, with 270,400 males and 298400 females. [15,17] the main economic activity is agriculture, farming in coffee, beans, Matooke, onions among others. Mbale is also a commercial and administrative city situated along a highway that joins Kenya to the Democratic Republic of Congo and South Sudan through Uganda.…”
Section: Study Setting / Sitementioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study conducted in Mbale Uganda, knowledge of the community toward COVID-19 was moderate and good which had a positive impact on the pandemic response. 16 Similarly, in a study conducted in Zimbabwe, the spread of myth and untrusted information related to COVID-19 had an undesirable impact on the people. 17 …”
Section: Introductionmentioning
confidence: 99%